The Validity of E-Commerce Sales Under Islamic Law - Daradjat, Reza Fasha; Firdaus, Sunny Ummul; Mulyanto, Mulyanto - (Faculty of Law, Universitas Pekalongan, 2024)
This study examines and analyzes the validity of e-commerce sales agreements in the context of Islamic law. The method used in this study uses normative research with a legislative approach, by studying primary and secondary legal materials. The findings of this study indicate that the advances in technology and information encourage merchants to innovate in transactions. E-commerce is any form of trade transaction or business of goods or services using electronic media without face-to-face alternating with modern ways of working using existing technological developments. (tidak bertatap muka). In Islam, the terms of an agreement include: bekwaamheid, toesremming, bepaalde onderwerp, and the existence of a justified cause (georloofde oorzak). The application of E-Commerce that utilizes technological advances in the creation of authentic acts in the cyber world under Article 15 paragraph (3) of the UUJN opens the opportunity to be organized, plus the existence of the ITE Act on the arrangement of electronic transactions, electronic documents and digital signatures. Meanwhile in E-Commerce in the view of the principles of Islamic law referring to the Quran and Hadith, its implementation can be carried out with the principle of mashlahah because of human needs in accordance with the demands of the development of an era that is always developing dynamically by means of interpretation ijtihad both textual and contextual. Islam is a religion that appreciates modernization as long as it must remain in accordance with the values of Islamic Shariah.